Judicial attempt at reconciliation of spouses - Krzywkowska, Justyna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
Existing canonical regulations emphasise the concern of the church legislator to avoid disputes among the faithful and to settle them peacefully (canon 1446 of the Code of Canon Law of John Paul II). In particular, this concern applies to reconciliation of spouses. First of all, the legislator imposes this obligation on the diocesan bishop, who is the first judge in the diocese and has ordinary, proper, and immediate power. At the beginning of a case brought before a church court, each judge should attempt to reconcile spouses through mediation or other means (e.g. conversation with a priest, meeting with an expert witness, marriage therapy, individual therapy). All pastoral measures should be applied not only before the start of a marriage annulment case, but also during the trial, if there is hope for reconciliation between the spouses. Unfortunately, church courts in Poland limit this norm to sending the defendant an inquiry about whether they intend to reconcile with their spouse and on what conditions. The spouse receives this inquiry along with the plaintiff’s complaint, which in most cases, casts a negative light on them. Most claims for annulment of marriage are still brought by the plaintiff for annulment on the part of the defendant. This article aims to present the attempt to reconcile spouses in the church forum.